Production and operations management - Panneerselvam, R (PHI, 2012)
2. Product Design and Analysis 3. Capacity Planning and Investment Decisions 4. Forecasting 5. Facility Location 6. Plant Layout and Materials Handling 7. Line Balancing 8. Line of Balance 9. Materials Management and Inventory Control 10. Aggregate Planning and Master Production Scheduling 11. Materials Requirements Planning 12. Production Planning and Control 13. Single Machine Scheduling 14. Flow Shop Scheduling 15. Job Shop Scheduling 16. Project Management 17. Work Study 18. Quality Control 19. Maintenance Planning and Control 20. Modern Production Management Tools